Enhancing Security and Privacy in Smart Factory: A Blockchain Based Solution - Durgesh R. Shukla; Avneesh Singh (International Journal of Wireless Security and Networks, 2024)
The manufacturing industry is currently experiencing a transformative shift due to the rise of smart factories, propelled by interconnected devices and automated systems. However, this integration of diverse technologies within smart factories introduces significant concerns regarding security and privacy. This research paper thoroughly investigates the vulnerabilities and threats prevalent in smart factory ecosystems, shedding light on the potential risks associated with centralized data storage and communication channels. The study emphasizes the critical need to address these security challenges to safeguard sensitive information and ensure uninterrupted operations in smart manufacturing environments. To this end, a comprehensive blockchain-based solution is proposed, strategically structured to facilitate seamless interactions among devices, sensors, and systems within the smart factory framework. Leveraging advanced cryptographic techniques and smart contracts, this solution aims to uphold the pillars of data integrity, confidentiality, and traceability. By implementing blockchain technology, the proposed solution offers robust protection against unauthorized access, tampering, and data breaches, thereby bolstering the resilience of smart factories against evolving cyber threats. This research not only identifies key security concerns in smart manufacturing but also provides a tangible framework for mitigating risks and enhancing the overall security posture of modern manufacturing facilities.
Keywords: Blockchain technology; Security and Privacy; industrial internet of things (IIoT); sensing layer; smart factory